2012
DOI: 10.1371/journal.pone.0050241
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Properties of Subicular GABAergic Currents Shape Hippocampal Output Firing Mode

Abstract: GABAergic function of the subiculum is central to the regulation of hippocampal output activity. Subicular neuronal networks are indeed under potent control by local inhibition. However, information about the properties of GABAergic currents generated by neurons of this parahippocampal area in normal tissue is still missing. Here, we describe GABAA receptor (GABAAR)-mediated phasic and tonic currents generated by principal cells (PCs) and interneurons (INs) of the rat subiculum. We show that in spite of simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…We previously reported that low-frequency stimulation targeting the subiculum alleviates sGS in the kindling and pilocarpine models (Zhong et al, 2012); it is therefore highly likely that the subiculum may serve as the ''choke point'' (Paz and Huguenard, 2015) for synchronous firing spreading from the hippocampus during sGS and play an important role in the control of sGS. The role of the subiculum in gating hippocampal output is largely contributed by its intrinsic microcircuits (Behr et al, 2009;Panuccio et al, 2012); that is, local GABAergic signaling reduces the propagation of afferent excitation and modulates the firing behavior of subicular pyramidal neurons. Although degeneration of various inhibitory interneuron populations in the subiculum has been shown in TLE (de Guzman et al, 2006;Knopp et al, 2008), the role of the subiculum with cellular precision in causal underpinnings of sGS in TLE has not yet been investigated due to the lack of a specific approach.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that low-frequency stimulation targeting the subiculum alleviates sGS in the kindling and pilocarpine models (Zhong et al, 2012); it is therefore highly likely that the subiculum may serve as the ''choke point'' (Paz and Huguenard, 2015) for synchronous firing spreading from the hippocampus during sGS and play an important role in the control of sGS. The role of the subiculum in gating hippocampal output is largely contributed by its intrinsic microcircuits (Behr et al, 2009;Panuccio et al, 2012); that is, local GABAergic signaling reduces the propagation of afferent excitation and modulates the firing behavior of subicular pyramidal neurons. Although degeneration of various inhibitory interneuron populations in the subiculum has been shown in TLE (de Guzman et al, 2006;Knopp et al, 2008), the role of the subiculum with cellular precision in causal underpinnings of sGS in TLE has not yet been investigated due to the lack of a specific approach.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to isolate the tonic component of inhibition from the synaptic component in subicular pyramidal neurons using GABA A receptor antagonists. To this effect, we used a non‐competitive antagonist (picrotoxin) and competitive antagonist (gabazine) (Chandra et al ., ; Curia et al ., ; Panuccio et al ., ). Application of picrotoxin (100 μ m ) to slices revealed an outward shift of the holding current along with blockade of phasic currents ( n = 7, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, GABA can activate a distinct pool of extrasynaptic GABA A receptors to mediate a persistent ‘tonic’ form of inhibition. Picrotoxin‐sensitive tonic currents were recorded in subicular pyramidal neurons in acute rat hippocampal brain slices, consistent with previous reports of a tonic GABA A receptor‐mediated conductance in subicular pyramidal neurons (Panuccio et al ., ). The two major subunits involved in tonic GABA A currents in the hippocampus are α5 and δ subunits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the late phase, intensive phasic GABAergic inhibition (IPSPs) leading to the suppression of epileptiform activity was observed as shown in Figs . Tonic inhibition through the activation of extrasynaptic GABAergic receptors has been reported in the subiculum (Curia et al ., ; Panuccio et al ., ). The intensive γ‐aminobutyric acid (GABA) release at the inhibitory synapses may increase the spillover of GABA leading to additional inhibition of the post‐synaptic neurons through tonic inhibition.…”
Section: Resultsmentioning
confidence: 97%